Diseño metodológico para la simulación del balance hídrico de una represa: caso Tunja, Colombia - Osso-Rodríguez, María Camila; Cabrales-Arevalo, Sergio; Rosso-Murillo, John William (Revista Científica, 2017)
In this work, we use Monte Carlo simulation in order to model the water balance of a dam, which provides water for human consumption to Tunja in Colombia. This model predicts that the best alternative source of water for human consumption for next 40 years in Tunja is La Copa dam. The authors developed a method to adjust our results to precipitations, infiltration, runoff, evapotranspiration, and the subsurface flow and extraction flow; into random variables. Our projections are realistic since Monte Carlo simulation allows us to model input and output flows from water balance, as stochastic variables, so including uncertainty associated with possible states of the nature; for example, weather conditions.